-x+6=-2x-12

Simple and best practice solution for -x+6=-2x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+6=-2x-12 equation:


Simplifying
-1x + 6 = -2x + -12

Reorder the terms:
6 + -1x = -2x + -12

Reorder the terms:
6 + -1x = -12 + -2x

Solving
6 + -1x = -12 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
6 + -1x + 2x = -12 + -2x + 2x

Combine like terms: -1x + 2x = 1x
6 + 1x = -12 + -2x + 2x

Combine like terms: -2x + 2x = 0
6 + 1x = -12 + 0
6 + 1x = -12

Add '-6' to each side of the equation.
6 + -6 + 1x = -12 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = -12 + -6
1x = -12 + -6

Combine like terms: -12 + -6 = -18
1x = -18

Divide each side by '1'.
x = -18

Simplifying
x = -18

See similar equations:

| -(3/x)=9 | | 4(b-2.1)=b+0.6 | | 3(3n-y)+1=31 | | (3r+8)(3r-8)= | | 2x^2-7=59 | | 7y=-4x | | 2(x+4)+2=8x+2(x+2) | | (7x+84)=112 | | 3x+2x-2=4x+x+2 | | -0.2-q=9q | | X*.05833333333=(X-113) | | N^7/10 | | 2g+3G=10 | | 4(-y+2)=-1 | | X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 |

Equations solver categories